Attenuation-density anomalous relationship of lead alkali borosilicate glasses. (September 2018) - Saddeek, Y.B.; Shaaban, K.H.S.; Elsaman, Reda; El-Taher, Atef; Amer, T.Z.
Abstract: The glass system 60 PbO – (40-x) SiO2 – x (0.1 Li2 O – 0.86 B2 O3 – 0.04 Dy2 O3 ) with 0 ≤  x  ≤ 30 mol% was synthesized and explored. Based on the FTIR analysis, the content of [BO4 ] structural units increased by a higher rate than that of [BO3 ] structural units upon the variation of the concentrations of (0.1 Li2 O – 0.86 B2 O3 – 0.04 Dy2 O3 ). The increase of the density and the decrease of the molar volume indicated a more compactness of the lead alkali borosilicate network. On the other hand, the attenuation coefficients of lead alkali borosilicate glasses have been measured for different gamma- ray photon energies (356, 662, 1173 and 1332 keV) using narrow beam transmission geometry. These coefficients were used in the determination of the mass attenuation coefficients, effective atomic number and effective electron density. The obtained results indicated that the values of the mass attenuation coefficients, the effective atomic number and effective electron density of the glass samples decreased with the increase in the B2 O3 concentration. Highlights: Penta-glass system 60 PbO – (40-x) SiO2 – x (0.1 Li2O – 0.86 B2O3 – 0.04 Dy2O3) were synthesized. The molar volume and FTIR had explored the structural variations of the explored glasses. The increase of the density and the decrease of the molar volume decreased. The attenuation coefficients of lead alkali borosilicate glasses have been measured for gamma- ray photon. The mass attenuation coefficients decrease with the increase in the B2O3 concentration.